PENGARUH MOTIVASI KERJA, DISIPLIN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL KECAMATAN LOWOKWARU - Gita Lestari; Hadi Sunaryo; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACTION The purpose of this study is to describe work motivation, work discipline, job satisfaction, and employee performance and to know the effect of work motivation, work discipline, and job satisfaction on the performance of employees partially or simultaneously.This research method using quantitative method. This research type is explanatory research. The sample of this research is Lowokwaru District civil servant by using saturated sampling, that is 32 respondents. Methods of data collection using questionnaires. The method of analysis used in this study is multiple regression analysis with SPSS 14.0 for windows. The results of this study indicate that: (1) There is a positive and insignificant effect of Work Motivation on the Performance of Civil Servants Lowokwaru District. (2) There is no influence of Work Discipline on Kinerrja of Civil Servant of Lowokwaru Subdistrict. (3) There is a positive and significant influence of Job Satisfaction on Performance of Civil Servant of Lowokwaru Subdistrict. Keywords: Work Motivation, Work Discipline, Job Satisfaction and Employee Performance